Research Paper: Recon for Me - Kakkar, Sanyam (Journal of Advanced Research in Information Technology, Systems and Management, 2023)
Getting to know the target system and acquiring information are the first steps in ethical hacking. The term “reconnaissance” refers to a collection of procedures and methods used to acquire and surreptitiously learn as much as possible about a target system, including enumeration, scanning, and foot printing. To find and steal sensitive information, reconnaissance is a crucial step. Attackers would have access to specific information during a proper recon. In this way, penetration testing in information security uses reconnaissance. An attacker utilises recon to communicate with the network’s open ports, active services, etc. to gather information without actively using the network. Accessing networks outside of the internet can be made easier with the information it offers. In essence, recon is a gold mine of important information that is vulnerable to intrusion.